Analysis of User Experience of the CapCut Application in Generation Z for Social Media Content Using the User Experience Questionnaire Method - Wulan, Damar; Syaifullah; Saputra, Eki; Rahmawita, Medyantiwi; Marsal, Arif (Scientific Journal of Informatics, 2024)
Purpose: In the midst of these dynamics of change, research, development and application of technology continues to be the main focus in efforts to achieve progress and efficiency in various sectors of life. Generation Z has been the primary architect of cultural and behavioral change on social media. One of the most prominent characteristics of Generation Z is their desire to create "viral" content on social media. Content created using CapCut often uses interesting video and audio effects, such as progress effects, dry effects, music effects, and so on. This application has various features that make it easier for users to create video content, such as video effects, audio and animation. This shows that generation Z tends to use the CapCut application to create and edit video content that they share on social media. This research was conducted based on a phenomenon that has recently occurred, where many generations Z want to create content on social media using the CapCut application and also from several previous studies that have been conducted which are still lacking in understanding CapCup user satisfaction as a medium for creating content for Generation Z. and from several interviews the author conducted with CapCut application users. Method: This research uses the user experience questionnaire (UEQ) method with six (6) variables, namely attractiveness, efficiency, clarity, dependability, stimulation and novelty. Dr. Martin Schrepp developed a special tool that can be used to analyze UEQ questionnaire results, namely the UEQ Data Analysis Tool. The UEQ Data Analysis Tool is in the form of an Excel application which can be obtained by downloading it directly from the official https://www.ueq-online.org/ website This study employs a quantitative research strategy. This study does not know the exact number of the population to be studied. So, the sample size was calculated using the Lemeshow formula, a survey was conducted on 96 users of the Capcut application. Result: Based on the results of the discussion regarding user experience, specifically Generation Z, in the CapCut Application using the User Experience Questionnaire (UEQ) method, conclusions can be drawn from the 6 variables in the UEQ used, the 6 variables obtained positive evaluation values, namely the Attractiveness (mean 1.177), Perspicuity variables. (mean 1.109), Efficiency (mean 1.109), Dependability (mean 1.159), Stimulation (mean 1.151) and Novelty (mean 0.763) with the highest evaluation value on the Attractiveness variable. 2. Based on the benchmark results, the values obtained for the Attractiveness variable were 1.18, Perspicuity 1.11, Efficiency 1.11, Dependability 1.16, Stimulation 1.15, and Novelty 0.76. Each variable gets an Above Average value (above the average). However, there is still potential for improvement to achieve standards of perfection desired. Users provided invaluable feedback and suggestions, highlighting the need for improvement. Novelty: This research provides 2 recommendations based on the results of evaluations using UEQ, which are expected to help in improving and improving the quality of the CapCut Application in the future.